Merangsang Rasa Tanggungjawab dengan I’m OK and You’re OK (Analisis Konseling Transaksional) - Ellyana Ilsan Eka Putri (Tarbiyatuna Kajian Pendidikan Islam, 2017)
Transactional analysis is one of the psycotheraphy approach in counseling. This approach emphasizes to promises and decision aspect trough promises, the goals and orietations of the theraphy process is developed by the counselees themselves, and also emphasizes the importance of counselees decisions taking. Transactional analysis was developed by Eric Berne at 1960. In developing this approace , Eric Berne has used various games between parents, adults and children, In the experiment, Berne tried to research and explain the ego status of parents, adults, and children in interaction environment, and also on how the interpersonal indication appeared in the daily life aspect, such as at family, work, school, etc.